Collaborative Strategies to Optimize Operating Room Turnover Time: A Systematic Review of Multidisciplinary Interventions - I Made Esa Sadana Yoga; Masyitoh Basabih (Media Publikasi Cendekia Indonesia, 2026)
Minimizing operating room turnover time (TOT) is crucial for optimizing surgical efficiency and improving clinical outcomes. Achieving this reduction heavily relies on effective multidisciplinary teamwork among surgical staff. This systematic review aims to evaluate various multidisciplinary collaboration strategies and their impact on decreasing TOT. Following the PRISMA guidelines and utilizing the JBI Critical Appraisal Checklist for quality assessment, a literature search was conducted across four databases for publications between 2015 and 2025. This yielded 16 eligible articles for analysis. The data synthesis evaluated collaboration models, intervention methods, and their specific effects on TOT. The analysis highlighted four primary strategies: (1) utilizing dedicated teams to build personnel familiarity, (2) applying structured communication during preoperative planning, (3) implementing parallel workflows for simultaneous collaboration, and (4) conducting systematic, coordination-based evaluations. These approaches were found to significantly reduce TOT. Healthcare facilities can adapt these strategies to their specific organizational contexts to enhance operational efficiency, cost-effectiveness, and patient safety. Future research should emphasize standardizing these collaborative frameworks across various hospital settings and surgical disciplines.